Development and use of a fully automatic clinical intelligent milk dispenser (一种全自动临床智能配奶机的研制与使用) - ZHANG Rongbang (张榕邦); OUYANG Li (欧阳丽); JIN Mu (金募); LIU Lingzhi (刘羚芷); LIN Yan (林妍); ZHANG Zhiyuan (张秩源) (中西医结合护理)
To design a new type of fully automatic intelligent milk dispenser that is different from traditional milk preparation methods, which is based on Internet technology and combined with artificial intelligence. Its structure mainly includes: shell, water tank, milk powder bucket, cover, mixing bin, sealer, control panel and heating transfer plate. Among them, the control panel includes a main control circuit board, a music sound and light module, a temperature display module, a milk/flush module, a temperature control module, and a wireless receiving module. The controls of these control panels are all connected to the main control circuit board. Compared with the traditional intelligent milk dispenser, this method incorporates functions such as high-pressure steam sterilization, automatic micro-stirring, remote control, and automatic bottle sealing in the operation, making the process more scientific and reasonable. More importantly, it helps to reduce the tedious workload of medical staff, reduce environmental pollution, and reduce the risk of intestinal infections in infants and young children. (本文介绍一种区别于传统配奶方式、基于互联网技术并结合人工智能的一种新型全自动智能配奶机的研制和应用方法。其结构主要包括: 壳体、水箱、奶粉桶、罩体、混合仓、封口器、控制面板以及加热传送板。其中, 控制面板包括主控电路板、音乐声光模块、温度显示模块、冲奶/冲水模块、温度控制模块和无线接收模块等, 这些控制面板的控件均与主控电路板相接。与传统的智能配奶机相比较, 该方式在操作中融入了紫外线消毒、自动微型搅拌、远程遥控、自动封瓶等功能, 使过程更为科学合理。更重要的是, 有利于减少医护人员繁琐的工作量, 减少对环境的污染, 降低婴幼儿肠道感染的风险。)